SYSTEMATIC REVIEW OF ENTREPRENURIAL MARKETING - Aftab, Muhammad; Abdullah, Abdul Aziz bin; Sarwar, Dr. Javaria; Sanaullah, Asif; Farid, Gohar; Bilal, Muhammad (The journal of contemporary issues in business and government, 2021)
Marketing is considered to be one of the most critical tasks for minor plus medium-sized enterprises in terms of growth as well as development, but it is also considered to be the biggest challenge for SMEs. Shortage of possessions, expertise and expertise, it is hard for SMEs to carry out traditional marketing activities. As a result, working in an atmosphere of aggregate dynamics, turbulence and competitiveness means that entrepreneurs with innovative creative concepts and attitudes, such as Entrepreneurial Marketing, have to overcome and modify conventional marketing principles (EM). When conventional marketing does not support small and medium enterprises (SME) then here is A new area of exploration that initiated by combination of marketing and entrepreneurship is Entrepreneurial marketing. The main purpose of this essay is the notion that can be found in literature like types, dimensions of Entrepreneurial marketing and major differences b/w Entrepreneurial marketing and conventional marketing. It also give a brief view about the history of basis of different new fields and in the last it focuses on the significance of small and medium enterprise with reference to the modern standard. The main objective of this study is to provide guideline to small and medium enterprises and give suggestion to them about future research direction in the same field.